2020
DOI: 10.1021/jacs.9b11637
|View full text |Cite
|
Sign up to set email alerts
|

The Doping Mechanism of Halide Perovskite Unveiled by Alkaline Earth Metals

Abstract: Halide perovskites are a strong candidate for the next generation of photovoltaics. Chemical doping of halide perovskites is an established strategy to prepare the highest efficiency and most stable perovskite-based solar cells. In this study, we unveil the doping mechanism of halide perovskites using a series of alkaline earth metals. We find that low doping levels enable the incorporation of the dopant within the perovskite lattice, whereas high doping concentrations induce surface segregation. The threshold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
174
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(181 citation statements)
references
References 58 publications
6
174
0
Order By: Relevance
“…Moreover, the carrier trapping is apparently relatively deep, and their detrapping and extraction are very slow; therefore, they cause only a weak, slow photocurrent component in TPC measurements in comparison with the high trapped carrier concentration revealed by TDCF measurements. Such trap properties are also in agreement with the segregation model proposed in Phung et al [17] Figure 4 summarizes results in a simple representative model (note that the SEM image does not correspond to the actual Sr 2þ concentration sample but is used as a base for the schematic). Here, the green arrow shows the direction of an electric field.…”
supporting
confidence: 86%
“…Moreover, the carrier trapping is apparently relatively deep, and their detrapping and extraction are very slow; therefore, they cause only a weak, slow photocurrent component in TPC measurements in comparison with the high trapped carrier concentration revealed by TDCF measurements. Such trap properties are also in agreement with the segregation model proposed in Phung et al [17] Figure 4 summarizes results in a simple representative model (note that the SEM image does not correspond to the actual Sr 2þ concentration sample but is used as a base for the schematic). Here, the green arrow shows the direction of an electric field.…”
supporting
confidence: 86%
“…Although no change in the PL emission or optical bandgap was observed, small amounts of Sr 2+ in the perovskite lattice may account for the improved device stability: increasing the strength of ionic bonds within the unit cell can decrease ion migration. This partial Sr 2+ incorporation is unexpected as recent work on the mechanism of Sr 2+ perovskite doping in conventional PSCs found that such high doping levels induce SrCl 2 surface segregation with negligible lattice incorporation [95]. The unexpected partial incorporation of Sr 2+ into the lattice is possibly due to the vastly different annealing procedures used for mCPSCs.…”
Section: Inorganic Additivesmentioning
confidence: 94%
“…Whereas substitution refers to an ion that sits within the bulk ABX3 lattice framework, additives are either removed during annealing or sit at interfaces or in interstitial sites. The terms are often used interchangeably, possibly because some species can act in both ways, with some of the added material incorporating into the lattice and the rest collecting at grain boundaries and other interfaces [95]. Other molecules, such as AVA, partially integrate into the lattice at grain boundaries via functional groups [27].…”
Section: Modifications To the Perovskite Formulation 31 Perovskite mentioning
confidence: 99%
“…All CsPbBr 3 films with and without lamination exhibited three main diffraction peaks corresponding to the (100), (110), and (200) planes. No noticeable peak shift was observed after the heat-only process or the lamination process, indicating the absence of lattice macrostrain or homogenous changes in the crystal structure [28]. Although it is hard to rule out the possibility that the strain induced by hot-pressing might be released once the laminates were separated, such a possibility is quite small according to prior work [22].…”
Section: Resultsmentioning
confidence: 97%